Efek Samping Hematologi Akibat Kemoterapi dan Tatalaksananya : [Hemathologic Adverse Effect Related to Chemotherapy] - Anna Febriani; Yuly Rahmawati (Faculty of Medicine Universitas Airlangga, 2019)
Lung cancer is the leading cause of cancer death in Asia. In Indonesia, it contributes the highest number to cancer incidence in male and is ranked fifth in female cancer incidence. Determinated attempts have been delivered to eliminate cancer with chemotherapy being the most important management strategy for advance stage lung cancer. As most medicines come with side effects, so does chemotherapy. Beside killing the target cells, the cytotoxic compound of cancer drug may also seriously alter normal cells. Therefore, formidable toxic effect of chemotherapy to normal tissue becomes the main problem, which clinicians should consider. Myelotoxicity is one of the most common chemotherapy-induced adverse events. It takes place in bone marrow-producing regions causing netropenia, thrombocytopenia and anemia. Each of those cytopenias requires separate intervention. This article will review the physiology of hematopoiesis, pathophysiology of cytopenias, and current guidelines and recommendations for prevention and treatment of myelotoxicity of cytotoxic chemotherapy.